Values and Behavior Among Minorities in Southwest China: A Cross-Cultural Validation of the Refined Value Theory - Yang, Yanli; Zhou, Jia; Feng, Pan; Jiang, Guangyu; Long, Yan; Zheng, Yong (Frontiers in Psychology, 2019)
The minorities in Southwest China are characterized by a blend of diverse cultures. It is not clear how values predict behaviors in such a population. We applied Schwartz’s refined value theory to assess the association between values and behaviors. Respondents (N = 532) reported values using the Portrait Values Questionnaire and rated their postulated behaviors with the Everyday Behavior Questionnaire. A confirmatory factor analysis validated the discriminant validity of 19 refined values. Multidimensional scaling analyses revealed a circular motivational structure with national characteristics. More importantly, the correlation analysis showed that 13 of 19 values correlated most strongly with its postulated or adjacent behaviors, which supported the cross-cultural prediction of behaviors by values. Variations differing from theoretical structure and the moderating of value-behavior relations by gender better reflected the effects of Chinese traditional culture, such as harmony, benevolence, and “the Golden Mean.” The results of this study enrich the cross-cultural validity of the refined value theory among Chinese minorities and enhanced our understanding of the multiculturally influenced minority population.